2006
DOI: 10.1192/bjp.188.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure in pre-school children in a war zone

Abstract: BackgroundThere has been little reported research into the effect of war on the behaviour and emotional well-being of pre-school children.AimsTo investigate the relationship between exposure to war trauma and behavioural and emotional problems among pre-school children.MethodAtotal of 309 children aged 3–6 years were selected from kindergartens in the Gaza Strip, and were assessed by parental reports in regard to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…The most common psycho-social disorders belong to the traumatic category: Post Traumatic Stress Disorder, Acute Stress Disorder, Traumatic Depression, somatization and so on. The disorders that affect Palestinian children are typical of daily exposure to relentless and extreme traumatic events (Thabet, Karim, & Vostanis, 2006). Experts in the field have illustrated how most Palestinian children suffer from emotional, behavioural and psychosomatic trauma-related disorders (Espie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most common psycho-social disorders belong to the traumatic category: Post Traumatic Stress Disorder, Acute Stress Disorder, Traumatic Depression, somatization and so on. The disorders that affect Palestinian children are typical of daily exposure to relentless and extreme traumatic events (Thabet, Karim, & Vostanis, 2006). Experts in the field have illustrated how most Palestinian children suffer from emotional, behavioural and psychosomatic trauma-related disorders (Espie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The reactions to being exposed to violence intensify with increasing level and duration of violence [14,17-19]. In 2003, Thabet examined the behavioral and emotional problems of 309 Palestinian preschoolers and found that direct and indirect exposure to war trauma increases the risk of poor mental health [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Although preschool children are highly vulnerable to the effects of traumatic events, the effects of maternal psychopathology on preschool children exposed to terrorism are not as yet well understood (Chemtob, Nomura, & Abramovitz, 2008; DeVoe, Bannon, & Klein, 2006; Fremont, 2004; Laor, Wolmer, & Cohen, 2001; Pfefferbaum, 2005; Pine, Costello, & Masten, 2005; Thabet, Karim, & Vostanis, 2006). …”
mentioning
confidence: 99%